Conservatism : Burke, Nozick, Bush, Blair? - Honderich, Ted (Pluto, 2005)
In this text, Ted Honderich, Britain's pre-eminent progressive political philosopher explores the distinctions of conservatism, seeking the fundamental principle that unifies it and is its rationale and foundation.